Unlocking the Potential of Artificial Intelligence in Democratizing Health Information: A Scholarly Synthesis - Windah, Andi; Nurhaida, Ida (International Journal of Educational Research & Social Sciences, 2025)
This study looks at how Artificial Intelligence (AI) can help make health information more accessible to everyone.  By using artificial intelligence, medical information can be made easier to understand and more available to everyone.  The study uses a literature review method.  It carefully chooses articles published from 2020 to 2024 from trusted academic databases like EBSCO, ScienceDirect, and ProQuest.  The articles were chosen based on how relevant they were and the latest developments in using AI for sharing health information.  The results show that AI can effectively translate complex medical words, offer personalized health information, and overcome language barriers using advanced language technology.  Also, AI can help disadvantaged communities by making it easier for them to get health information and by reducing the spread of false information using fact-checking programs.  The study highlights how important interactive AI tools are for getting users involved and shows how these tools can be used for data-driven public health projects.  This study shows that AI can play a big role in creating a fairer and better-informed society.  In conclusion, the study highlights how important it is to think about ethics and to share fair and accurate information.